The directive speech acts used in english speaking class - Muhammad Khatib Bayanuddin; Jamaluddin Jamaluddin; Hilma Suryani (IJER (Indonesian Journal of Educational Research), 2016)
This research discusses about an analysis of the directive speech acts used in english speaking class at the third semester of english speaking class of english study program of IAIN STS Jambi. The aims of this research are to describe the types of directive speech acts and politeness strategies that found in English speaking class. This research used descriptive qualitative method. This method used to describe clearly about the types and politeness strategies of directive speech acts based on the data in English speaking class. The result showed that in English speaking class that there are some types and politeness strategies of directive speech acts, such as: requestives, questions, requirements, prohibitives, permissives, and advisores as types, as well as on-record indirect strategies (prediction statement, strong obligation statement, possibility statement, weaker obligation statement, volitional statement), direct strategies (imperative, performative), and nonsentential strategies as politeness strategies. The achievement of this research are hoped can be additional knowledge about linguistics study, especially in directive speech acts and can be developed for future researches. Key words: directive speech acts, types, politeness strategies.